Developing youth justice policy and programme design in Australia. Issue 2 (13th November 2021) - Butcher, Luke; Day, Andrew; Miles, Debra; Kidd, Garry; Stanton, Steven
Abstract: The national Closing the Gap reform provides a mandate for mainstream organisations to undergo structural transformation to better address the needs and concerns of Aboriginal and Torres Strait Islander communities. In the criminal justice sector, the reform resonates strongly with ongoing discussions about how both policy and practice can address the significant over‐representation of Aboriginal people across the criminal justice system. One way that structural transformation can occur is through the genuine involvement of Aboriginal knowledge holders and communities in policy development. This study illustrates how this might happen in relation to youth justice policy and programme design. Eighteen Aboriginal community members from a town in rural New South Wales participated in a series of interviews relevant to the Closing the Gap target. Qualitative content analysis was used to identify four key themes relevant to the development of justice policy: supporting cultural identity in a post‐colonial context; articulating strengths and resources which can be mobilised in the community; the centrality of poverty to offending; and responding to intergenerational trauma. The study illustrates how non‐Indigenous policymakers and practitioners might approach the task of engagement and consultation by identifying Aboriginal knowledge as a legitimate epistemic resource that they can draw upon to guide the ongoing development of evidence‐based policy and programmes. Abstract : This study describes how an approach to community engagement using a culturally informed research methodology to develop a locally informed theory of change can guide youth justice policy.